Seasonal Variations in Insect and Earthworm Communities in Agricultural Soils of Sheikhupura District, Punjab, Pakistan - Fatima, Ghazal; Imam, Faiza; Abbas, Aqsa; Tahir, Syed Waqqas (Biological and Clinical Sciences Research Journal, 2025)
Soil biodiversity plays a crucial role in maintaining agricultural productivity and ecosystem stability; however, information on the seasonal dynamics of soil fauna in Pakistani agroecosystems remains limited. Objective: To evaluate the seasonal variation in insect and earthworm communities and their relationship with key soil environmental factors in major crop systems of Punjab, Pakistan. Methods: A field-based observational study was conducted in agricultural soils of Sheikhupura district, Punjab, under wheat–rice and wheat–maize cropping systems. Surveys were carried out during spring, summer, autumn, and winter. Insect fauna were sampled using pitfall traps, while earthworms were collected through soil monolith extraction. Faunal abundance, diversity, density, and biomass were assessed. Soil moisture, temperature, and organic matter were measured concurrently. Data were analyzed using two-way analysis of variance to determine seasonal effects. Pearson correlation analysis evaluated associations between soil variables and earthworm parameters, while stepwise multiple regression analysis identified predictors of earthworm biomass. Statistical significance was set at p < 0.05. Results: Season exerted a significant effect on all soil faunal parameters (p < 0.001). The lowest mean insect abundance was observed in summer (162.17 ± 37.58 individuals), whereas the highest values were recorded in spring (329.50 ± 10.48 individuals) and autumn (321.67 ± 38.44 individuals). Insect taxonomic richness was lowest in winter (12.33 ± 2.07 taxa). Earthworm population density peaked during autumn (97.17 ± 20.16 individuals m⁻²) and winter (92.00 ± 13.52 individuals m⁻²), while the lowest density occurred in summer (26.33 ± 16.86 individuals m⁻²). Earthworm biomass followed a similar seasonal trend, with the highest value in autumn (111.42 ± 18.69 g m⁻²). Soil moisture showed a strong positive correlation with earthworm density (r = 0.742, p < 0.001), whereas soil temperature was negatively correlated (r = −0.618, p = 0.002). Soil moisture, temperature, and organic matter collectively explained 79% of the variation in earthworm biomass (R² = 0.79). Conclusion: Seasonal climatic factors strongly regulate insect and earthworm communities in semi-arid agroecosystems of Pakistan. These findings highlight the ecological importance of seasonal dynamics in shaping soil biodiversity and emphasize the need to incorporate climate-sensitive strategies into sustainable soil management practices.